Existence of periodic solutions for Rayleigh equations with state-dependent delay - Jehad O. Alzabut; Cemil Tunc (Electronic Journal of Differential Equations, 2012)
We establish sufficient conditions for the existence of periodic solutions for a Rayleigh-type equation with state-dependent delay. Our approach is based on the continuation theorem in degree theory, and some analysis techniques. An example illustrates that our approach to this problem is new.